P14ARF induces apoptosis via an entirely caspase‐3‐dependent mitochondrial amplification loop. Issue 11 (1st August 2013) - Milojkovic, Ana; Hemmati, Philipp G.; Müer, Annika; Overkamp, Tim; Chumduri, Cindrilla; Jänicke, Reiner U.; Gillissen, Bernd; Daniel, Peter T.
<x xml:space="preserve">Abstract</x> The p14ARF tumor suppressor triggers cell death or cell cycle arrest upon oncogenic stress. In MCF‐7 breast carcinoma cells, expression of the tumor suppressor gene p14ARF fails to trigger apoptosis but induces an arrest in the G1 and, to a lesser extent, in the G2 phase in the cell division cycle. Here, inhibition of cell cycle arrest resulted in apoptosis induction in caspase‐3 proficient MCF‐7 cells upon expression of p14ARF. This occurred in the absence of S‐phase progression or mitotic entry. In contrast, syngeneic, caspase‐3‐deficient MCF‐7 cells remained entirely resistant to p14ARF‐induced apoptosis. Thus, cell cycle checkpoint abrogation overcomes resistance to p14ARF‐induced cell death and promotes cell death via a caspase‐3‐dependent pathway. Cell death coincided with dissipation of the mitochondrial membrane potential, release of cytochrome c, and was inhibitable by pan‐caspase inhibitors and the caspase‐3/7 inhibitor zDEVD‐fmk. Of note, mitochondrial events of apoptosis execution depended entirely on caspase‐3 proficiency indicating that caspase‐3 either acts "up‐stream" of the mitochondria in a "non‐canonical" pathway or mediates a mitochondrial feedback loop to amplify the apoptotic caspase signal in p14ARF‐induced stress signaling.